De Jure vs. De Facto Rights: A Response to "Human Rights: What the United States Might Learn from the Rest of the World and, Yes, from American Sociology"1. Issue 1 (26th August 2016) - Armaline, William T.; Glasberg, Davita Silfen; Purkayastha, Bandana
Abstract : Blau's (2016 ) argument for a Constitutional Project implies that changes in the U.S. Constitution would ensure fundamental adherence to human rights standards. We disagree with the assumption that legal and institutional instruments are guarantors of human rights practice. Instead, we see rights practices as the function of power struggles that include but go far beyond formal law. Instead, we emphasize an important distinction between de jure human rights instruments and de facto human rights practice, arguing that the focus on de jure instruments and legal discourse misses the significant effect of social movements and direct action that secure rights practice. De jure instruments may codify human rights and enumerate them as important, but they do not carry the authority of enforcement. We argue that the pursuit of human rights must be reframed to include both de jure and de facto human rights terrains. While charitable provisions from generous states can temporarily relieve specific human rights abuses, universal human rights practice requires establishing the fundamental political primacy of the people through the processes of the human rights enterprise.